Penerapan Pancasila Mind Chart Upaya Peningkatan Pemahaman Sejarah Lahirnya Pancasila Murid Kelas 5 - Zahra Rika Karmelia; Eva Dwi Suryani; Susilo Tri Widodo; Amos Kurniawan (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
This classroom action research aimed to improve students’ understanding of the historical process of the establishment of Pancasila through the implementation of the Pancasila Mind Chart as a visual learning medium. The study was conducted with 28 fifth-grade students at SD Negeri Wonoplembon 02 and applied the Kemmis and McTaggart model consisting of planning, action, observation, and reflection over two cycles. The Pancasila Mind Chart was developed as a structured visual tool integrating key figures, chronology, and main ideas discussed during the BPUPKI and PPKI sessions. Data were collected through observation, written tests, interviews, and documentation. The results indicated a significant improvement in students’ cognitive and learning engagement. In Cycle I, the average score was 78, with students still showing difficulties in identifying key events and connecting the contributions of historical figures. After revision and strengthened guidance in Cycle II, the average score increased to 83, accompanied by improved student participation, clearer conceptual mapping, and more accurate historical explanations. Students demonstrated deeper understanding of chronological sequences and could connect the stages of Pancasila’s formulation more independently. These findings confirm that the Pancasila Mind Chart is an effective medium for enhancing historical comprehension, critical thinking, and student engagement in Pancasila Education. The study recommends the broader use of structured visual media in teaching complex historical concepts at the elementary school level.